Efficacy and Safety of Posterior Long-Segment Fixation Versus Posterior Short-Segment Fixation for Kummell Disease: A Meta-Analysis. (2nd June 2022) - Yu, Yikang; Zeng, Hanbing; Guo, Enpin; Tang, Binbin; Fang, Yuan; Wu, Lianguo; Xu, Chao; Peng, Yi; Zhang, Bin; Liu, Zhen
Purpose: Posterior short-segment fixation (SSF) and long-segment fixation (LSF) are two methods for the treatment of Kummell disease, but the safety and effectiveness of these two surgical methods still lack adequate medical evidence. This study aimed to evaluate the two methods. Methods: Database searches for randomized controlled trials, case-control studies, and cohort studies of posterior SSF and posterior LSF in the treatment of Kummell disease were performed. After the document quality was evaluated with the Newcastle-Ottawa Quality Assessment Scale, a meta-analysis was carried out. Results: Meta-analysis revealed that the operation time and intraoperative blood loss in the LSF group were higher than those in the SSF group [MD = −18.17, 95% CI (−30.31, −6.03), z = 2.93, P = .003; MD = −82.07, 95% CI (−106.91, −57.24], z = 6.48, P < .00001). The postoperative last follow-up local kyphosis angle in the SSF group was greater than that in the LSF group (MD = 3.18, 95% CI [.56, 5.81], z = 2.38, P = .02), and there were no significant differences in perioperative complications, bone cement leakage rate, incidence of adverse events during follow-up, postoperative follow-up visual analog scale, postoperative Oswestry dysfunction index, and postoperative immediate local kyphosis angle between the two groups ( P > .05). Conclusion: SSF and LSF are effective and safe for the treatment of Kummell disease. SSF can reduce the operation time and intraoperative bleeding; LSF can better maintain the long-term stability of kyphosis. The methods should be evaluated by clinicians according to the individual situation of the patients.